THE TRANSFORMATION OF LANGUAGE LEARNING THROUGH DIGITAL LITERACY: AN ANALYSIS OF THE ROLE OF TECHNOLOGY AND ARTIFICIAL INTELLIGENCE IN ENHANCING STUDENTS’ LANGUAGE COMPETENCE IN THE ERA OF INDEPENDENT LEARNING - Fitria Meisarah; Didi Sudrajat; Dedi Sukma Wijaya (CV. Adiba Aisha Amira, 2026)
This article analyses the transformation of digital literacy-based language learning through the role of technology and artificial intelligence (AI) in enhancing students’ language competencies in the era of the Merdeka Belajar Curriculum. Using a descriptive-analytical literature review approach, it was found that digital literacy is revolutionising the learning paradigm from teacher-centred to student-centred through interactive media such as e-books, collaborative platforms, and problem-based projects that holistically hone the four language skills. AI technology, through chatbots, speech recognition, and automated writing evaluation, provides adaptive learning, instant feedback, and gamification that boosts motivation and learning efficiency by up to 40%, despite facing challenges such as the digital divide, teacher competence, and academic ethics. This transformation supports the vision of the Pancasila Student Profile towards the golden generation of 2045, with recommendations for digital pedagogy training, equitable infrastructure, and strict AI regulations.